Morpho-phylogenetic identification and characterization of new causal agents of Fusarium species for postharvest fruit rot disease of muskmelon in northern Thailand and their sensitivity to fungicides - Suwannarach, Nakarin; Khuna, Surapong; Thitla, Tanapol; Senwanna, Chanokned; Nuangmek, Wipornpan; Kumla, Jaturong; Lumyong, Saisamorn (Frontiers in Plant Science, 2024)
A significant global problem affecting muskmelon (Cucumis melo L.) is fruit rot caused by phytopathogenic fungi, which results in unsaleable products and substantial financial losses. In 2022 and 2023, fruit rot on muskmelon was found during the postharvest storage period in Phayao Province of northern Thailand. The aim of the current study was to isolate the species of fungi causing the fruit rot lesions. Out of the rot lesions on muskmelons, nine fungal isolates were received. All isolates of fungi were identified through a combination of morphological characteristics and molecular analyses. Based on its morphological traits, all isolated fungal isolate was assigned to the genus Fusarium. All the fungal isolates were determined to belong to the Fusarium incarnatum-equiseti species complex through multi-gene phylogenetic analysis employing the calmodulin (cam), RNA polymerase second largest subunit (rpb2), and translation elongation factor 1-alpha (tef1-α) genes. These isolates were identified as F. compactum (SDBR-CMU483), F. jinanense (SDBR-CMU484, SDBR-CMU485, and SDBR-CMU486), F. mianyangense (SDBR-CMU487 and SDBR-CMU488), and F. sulawesiense (SDBR-CMU489, SDBR-CMU490, and SDBR-CMU491). Moreover, pathogenicity tests were subsequently carried out, and the results indicated that all fungal isolates caused symptoms of fruit rot on inoculated muskmelon fruits. Notably, this result was consistent with the symptoms observed throughout the postharvest storage period. In the fungicide screening test, all fungal isolates showed sensitivity to copper oxychloride. However, all isolates showed insensitivity to benalaxyl-M + mancozeb, carbendazim, mancozeb, and metalaxy. To the best of our knowledge, the present study is the first to identify F. compactum, F. jinanense, and F. mianyangense as new causative agents of muskmelon fruit rot in Thailand and other regions globally. This is also the first report of postharvest fruit rot on muskmelons caused by F. sulawesiense in Thailand. Furthermore, the fungicide screening results indicate that fungicide resistance can be beneficial in developing potential management strategies against postharvest fruit rot disease of muskmelon caused by these four pathogenic Fusarium species.